Cable aéreo: una alternativa de transporte sostenible entre las comunas 1, 12 y 13 de la ciudad de Ibagué (2021)
This document is based on providing knowledge in the framework of mobility, transport and public space, in order to generate guidelines that allow promoting an urban lifestyle focused on the integration between different modes of motorized and non-motorized public transport. motorized. Bearing in mind that transport is essential for economic and social development, since it generates opportunities for the less favored population and contributes to making economies more competitive. Transportation infrastructure connects people with workplaces, educational establishments, health services, recreation, and enables the distribution of goods and services throughout the world.